A window on the future of Geodesy : Proceedings of the International Association of Geodesy, IAG General Assembly, Sapporo, Japan, June 30 - July 11, 2003 - International Association of Geodesy. General Assembly (2003 : Sapporo-shi, Japan); Sanso, F. (Fernando), 1945- (New York : Springer, 2005)
PSZJBL